PROFIL PENYELESAIAN SOAL GEOMETRI SISWA YANG MEMILIKI KECERDASAN LOGIS MATEMATIS DOMINAN DITINJAU DARI PERBEDAAN JENIS KELAMIN - Umi Kalsum; Dasa Ismaimuza (Universitas Tadulako, 2021)
This study aims to obtain a description of solving geometry problems of male and female students who have dominant mathematical logical intelligence. The Subjects of this research consisted of a male student (S1) and a female student (S2) of X grade students of SMAN Model Terpadu Madani Palu who had dominant mathematical logical intelligence. This type of research is a qualitative descriptive study. The solving geometry problems data of the two subjects were obtained through geometry problems and unstructured interviews. The results showed that in completing SG1: S1 was more dominant in using his spatial abilities in solving SG1 01, SG1 03A, SG1 03B, and SG1 04, as well as integrating spatial abilities and mathematical logical abilities in solving SG1 02. Meanwhile, S2 is more dominant in using her spatial abilities in solving SG1 01 and SG1 04, integrating spatial abilities and mathematical logical abilities in solving SG1 02, and more dominantly using mathematical logical abilities in solving SG1 03A and SG1 03B.